Krill growth and condition in Western Indian Ocean sector of the Southern Ocean 30-80°E in austral summer 2006 - Patti Virtue; Kawaguchi, S; McIvor, JS; Nicol, S; Wotherspoon, S; Brown, M; Casper, R; Davenport, S; Finley, L; Foster, J; Yoshida, T; Yoshiki, T (2010)
Krill growth and physiological condition were measured during the Baseline Research on Oceanography, Krill and the Environment - West (BROKE-West) large-scale survey of the Western Indian Ocean sector (30-80 ï¿½E) of the Southern Ocean. Krill growth and condition were related to sea-surface temperature (SST) and Chlorophyll a levels. Estimates of Antarctic krill growth were obtained using the Instantaneous Growth Rate (IGR) technique, which reflects in situ growth of krill during the intermoult period prior to capture. A total of 10,362 krill were incubated in the IGR experiments conducted on board the research vessel. The average growth rate ranged between 1.8ï¿½9.6% of body length throughout the study area (n=1557). Juvenile and sub-adult krill showed higher growth rates compared to adults. Growth decreased with size for krill of all maturity classes, with the largest krill (total length >50 mm) expressing negative growth. On average, mean growth was higher (6.5%) in the western section (30-55ï¿½ E) of the study area compared to the east (56-80ï¿½ E) (4.2%). In the western section significantly higher growth rates were recorded for krill sampled close to the ice-edge (8.4%) compared to the open ocean (4.2%), which may be due to the presence of phytoplankton blooms associated with the retreating sea ice. However, in the eastern sector higher growth rates occurred in krill from the open ocean compared to the krill caught in areas closer to the coast (5.4% and 2.6% respectively). Krill condition was measured in terms of digestive gland size as a percentage of carapace length. The size of krill digestive gland relative to carapace length ranged from 0.46 to 0.66 (n=2403). A significant positive correlation was found between growth rate and size of the digestive gland (r2=0.7), indicating that growth is related to feeding events. Both digestive gland size and krill growth significantly increased with increasing Chlorophyll a levels and declining SST.